The linguistic situation of the Siberian Germans: on a Material of "objective" and "subjective" Data; Sociolinguistic symposium 21. Attitudes and Prestige - Alexandrov O. A. Oleg Anatolievich (General Paper Sessions, 2016)
Title screen